Composite material for solar concentrator and preparation method of composite material

By using composite materials of quartz glass, polymers, fluorescent materials and scattering materials in solar concentrators, the problems of poor adhesion and high light energy loss are solved, and higher adhesion and light conduction efficiency are achieved.

CN119490778AActive Publication Date: 2025-02-21ZHENGZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411425648.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-13
Publication Date
2025-02-21
Estimated Expiration
2044-10-13

AI Technical Summary

Technical Problem

In the existing solar fluorescent concentrators, the combination of fluorescent materials and optical waveguides has problems of poor adhesion and high light energy loss, and it is difficult for inorganic particles and organic polymers to prepare stable sols, resulting in uneven coatings.

Method used

The monomer is polymerized into long-chain polymers by thermal curing and initiator, and the monomer is polymerized into long-chain polymers by thermal curing and initiator. Improve adhesion and sol stability, and adjust the thickness and refractive index of the coating to reduce reflectivity.

Benefits of technology

It improves the adhesion of composite materials, reduces the reflectivity of the coating, reduces the loss of light energy, and improves the conduction efficiency of solar light, and enhances the photoelectric conversion efficiency of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490778A_ABST
    Figure CN119490778A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of organic and inorganic composite materials, and particularly relates to a composite material for a solar concentrator and a preparation method of the composite material. The composite material for the solar concentrator comprises quartz glass, a high-molecular polymer, a fluorescent material and a scattering material, wherein the high-molecular polymer is formed by thermally curing pentaerythritol triacrylate in the presence of an azodiisobutyronitrile initiator; the fluorescent material is composed of Tb < 3 + > doped hollow MgF2 nanoparticles. The scattering material is SiO2 particles with the particle size of 400 to 600 nm; the high-molecular polymer, the fluorescent material and the scattering material are compositely coated on the surface of the fluorescent quartz glass. The combined device can collect and conduct sunlight, and has important application value in the building and photovoltaic fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic and inorganic composite materials, and in particular relates to a composite material for a solar concentrator and a preparation method thereof. Background Art

[0002] At present, with the increasing environmental pollution and energy crisis, the development of green energy is imminent. Solar energy, a clean and environmentally friendly renewable energy, has received more and more attention, which has also promoted the rapid development of solar energy technology. Solar cells can convert solar energy into electrical energy. However, most solar cells directly receive sunlight, which requires a large number of cells, is costly, and occupies a large area. How to efficiently collect sunlight and reduce the cost of solar cells is a major challenge.

[0003] Solar fluorescent concentrators (LSCs) are a promising light-concentrating device. They are coupled with small-area solar cells for efficient solar-to-electrical energy conversion. LSCs are composed of fluorescent materials, optical waveguides, and solar cells. When the fluorescent concentrator is illuminated, the fluorescent material absorbs and re-emits light through fluorescence. Due to total internal reflection, it is guided to the edge of the concentrator, where the edge is connected to the cell. That is, without increasing the area of ​​the solar cell, the area of ​​the concentrator is increased to improve the utilization of light energy.

[0004] Most combinations of fluorescent materials and optical waveguides are to coat inorganic luminescent particles on the surface of the optical waveguide material. However, direct coating of inorganic particles may result in poor adhesion to the surface of the optical waveguide and easy falling off. The coating prepared by combining organic polymers with inorganic particles can improve the adhesion of the coating, but the polymer will fill the gaps between the inorganic particles, which will increase the refractive index of the coating, thereby increasing the reflection of light and causing light energy loss. In addition, it is difficult to prepare a stable sol due to the different polarities of inorganic particles and organic polymers, making it difficult to prepare a uniform coating, resulting in increased scattering. Summary of the invention

[0005] In order to overcome the disadvantages of the prior art, the present invention provides a composite material for a solar concentrator and a preparation method thereof.

[0006] The technical solution adopted by the present invention to solve the technical problem is as follows:

[0007] The composite material for solar concentrator comprises quartz glass, high molecular polymer, fluorescent material and scattering material, wherein the high molecular polymer is formed by thermal curing pentaerythritol triacrylate under the initiator of azobisisobutyronitrile; the fluorescent material is formed by Tb 3+The invention is composed of doped hollow MgF2 nanoparticles; the scattering material is SiO2 particles of 400-600nm; the high molecular polymer, fluorescent material and scattering material are compositely coated on the surface of fluorescent quartz glass.

[0008] High molecular polymers can act as adhesives, thereby improving their adhesion. Hollow particles can reduce the refractive index of the coating, thereby improving the reflected light on the surface. Moreover, the combination of resin monomers and inorganic particles can avoid the direct combination of inorganic particles with long-chain polymers, thereby improving the stability of the sol. SiO2 particles of 400 to 600 nm can scatter light, allowing more scattered sunlight to be transmitted from quartz glass to solar cells.

[0009] It is further preferred as a composite material for solar concentrators.

[0010] Preferably, high molecular weight polymer, Tb 3+ , the masses of hollow MgF2 nanoparticles and SiO2 particles are:

[0011] High molecular weight polymer: 10 to 30 parts by weight;

[0012] Tb 3+ : 0.2-0.5 parts by mass;

[0013] Hollow MgF2 nanoparticles: 10-40 parts by mass;

[0014] SiO2 particles: 4 to 8 parts by mass.

[0015] The collocation of the above particles and the content of the high molecular polymer will directly affect the adhesion and refractive index of the coating. The more the high molecular polymer content is, the denser the coating is and the better the adhesion is, but the refractive index of the dense coating will be higher, resulting in an increase in its reflectivity. MgF2 is the bulk material with the lowest refractive index in nature that has been found, and the hollow MgF2 material can further reduce the refractive index, and its ratio can regulate the refractive index of the entire coating. In addition, fluoride is a good carrier for rare earth ion lattice doping, and is used as a fluorescent material in the present invention.

[0016] Preferably, the thickness of the high molecular polymer, fluorescent material and scattering material compositely coated on the surface of the fluorescent quartz glass is 400-700 nm.

[0017] The above thickness is critical, according to Fresnel's law of reflection: when the thickness and refractive index of the coating satisfy the following two formulas, the reflectivity will be minimized at a specific wavelength.

[0018] n1d=(2k+1)λ0 / 4, k=0, 1, 2, 3…

[0019] n1=(n0×n s )1 / 2

[0020] Where: n0, n1, n s , λ0 and d represent the refractive index of air, coating, quartz glass, wavelength of incident light and coating thickness respectively. The wavelength band of silicon solar cells is 380-1100nm. When k=0, the reflectivity decreases the widest, and the optimal thickness is 70-225nm. When k=1, the optimal thickness is 210-675nm. Theoretically, the average reflectivity is lowest when k=0. However, if the thickness is too thin, there are two problems: first, the size of the scattering particles is too large, and second, the light conversion and scattering are insufficient. Therefore, we choose a thickness of 210-675nm. However, the size of SiO2 particles is 400-600nm. Therefore, we adjust the thickness of the coating to 400-700nm. It can reduce the reflectivity and ensure its ability to collect light.

[0021] The present invention also provides a method for preparing a composite material for a solar concentrator, comprising the following steps:

[0022] S1. Preparation of MgF2:Tb 3+ Nanoparticles: magnesium acetate tetrahydrate, Tb2O3, n-propanol, hydrofluoric acid and hydrochloric acid are vigorously stirred and then poured into the polytetrafluoroethylene liner of the reactor. They are heated at 150-180°C for 6 hours. After the reaction is completed, MgF2:Tb 3+ Nanoparticles;

[0023] S2, preparation of SiO2 nanoparticles: tetraethyl orthosilicate, anhydrous ethanol and ammonia water, prepare SiO2 nanoparticles by hydrolysis polymerization, stir for 6 hours, and then age at room temperature for 2 days. Finally, centrifuge to obtain SiO2 nanoparticles;

[0024] S3, preparation of sol: take the MgF2:Tb obtained in step S1 3+ The nanoparticles and the SiO2 nanoparticles obtained in step S2 are dispersed in a mixed solvent of isopropanol and methyl isobutyl ketone, and after being stirred evenly, pentaerythritol triacrylate and azobisisobutyronitrile are added and stirred evenly to obtain a composite sol;

[0025] S4, coating: coating the composite sol on the surface of the quartz glass by 3 to 6 cycles of pulling by immersion pulling method;

[0026] S5. Curing: Place the glass sample in an oven at 80°C for 5 to 10 minutes.

[0027] The invention is further preferred as a method for preparing a composite material for a solar concentrator.

[0028] Preferably, the added amounts of magnesium acetate tetrahydrate, Tb2O3, n-propanol, hydrofluoric acid and hydrochloric acid in step S1 are 10-15 parts by mass, 0.1-0.25 parts by mass, 40 parts by mass, 4 parts by mass and 4 parts by mass, respectively.

[0029] Preferably, the added amounts of tetraethyl orthosilicate, anhydrous ethanol and aqueous ammonia in step S2 are 10-15 parts by mass, 40-60 parts by mass and 15-20 parts by mass, respectively.

[0030] Preferably, the MgF2:Tb in step S3 3+ The added amounts of nanoparticles, SiO2 nanoparticles, isopropyl alcohol, methyl isobutyl ketone, pentaerythritol triacrylate and azobisisobutyronitrile are 1-4 parts by mass, 0.4-0.8 parts by mass, 20-40 parts by mass, 10-20 parts by mass, 1-3 parts by mass and 0.1-0.3 parts by mass, respectively.

[0031] Preferably, the pulling speed of the immersion pulling method in step S4 is 75 to 150 mm / min.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) Compared with the original technology, the composite material coated on the quartz glass surface has better adhesion.

[0034] (2) Compared with the prior art, the present invention adjusts the thickness and refractive index of the coating, and the hollow MgF2 particles can be used as a fluorescent material and can also adjust the refractive index of the coating. When the thickness of the coating is appropriate, the reflectivity can be reduced, thereby reducing the loss of light energy.

[0035] (3) The composite material of the present invention is an inorganic particle MgF2:Tb 3+ , SiO2 particles and high molecular polymer. Since inorganic particles and long-chain organic polymers have different polarities, the prepared sol is not stable. In the present invention, polymer monomers are compounded with inorganic particles to make it more stable, and then the monomers are polymerized into long-chain high molecules through thermal curing and initiator. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a schematic diagram of the working principle of composite materials used in solar concentrators;

[0037] Figure 2 (a) is Tb prepared in Example 1 3+ Transmission electron micrograph of doped MgF2 nanoparticles, Figure 2 (b) is Tb 3+ Excitation spectrum of doped MgF2 nanoparticles, Figure 2 (c) is Tb in Example 1-43+ Emission spectrum of doped MgF2 nanoparticles, the inset is a photograph of the sample in Example 1 under 365nm UV light;

[0038] Figure 3 is a scanning electron microscope photograph of SiO2 particles prepared in Example 2;

[0039] Figure 4 (a) and 4(b) are scanning electron microscope images of the coatings prepared in Comparative Example 1 and Example 3, respectively;

[0040] Figure 5 (a) and 5(b) are micrographs of the scratches of the coatings prepared in Comparative Example 1 and Example 3 under a 3H pencil, respectively;

[0041] Figure 6 is the reflectance spectra of the samples prepared in Examples 1 to 3 and Comparative Examples 2 to 3;

[0042] Figure 7 This is a photo of a composite material for solar concentrators under 365nm ultraviolet light;

[0043] Figure 8 It is the IV curve of the samples prepared in Examples 1 to 3. DETAILED DESCRIPTION

[0044] The present invention will be further described below in conjunction with comparative examples and embodiments.

[0045] Example 1

[0046] This embodiment provides a composite material for a solar concentrator and a preparation method thereof:

[0047] Composite material for solar concentrator: comprising quartz glass, high molecular polymer, fluorescent material and scattering material, wherein the high molecular polymer, Tb 3+ , the masses of hollow MgF2 nanoparticles and SiO2 are:

[0048] High molecular weight polymer: 10 parts by mass;

[0049] Tb 3+ : 0.2 parts by mass;

[0050] Hollow MgF2 nanoparticles: 10 parts by mass;

[0051] SiO2 particles: 4 parts by mass, size 400nm;

[0052] The thickness of the high molecular polymer, fluorescent material and scattering material compositely coated on the surface of the fluorescent quartz glass is 400nm.

[0053] The preparation method comprises the following steps:

[0054] S1. Preparation of MgF2:Tb 3+ Nanoparticles: 10 parts by mass of magnesium acetate tetrahydrate, 0.1 parts by mass of Tb2O3, 40 parts by mass of n-propanol, 4 parts by mass of hydrofluoric acid and 4 parts by mass of hydrochloric acid were vigorously stirred and then poured into the polytetrafluoroethylene liner of the reactor and heated at 150°C for 6 hours. After the reaction was completed, MgF2:Tb 3+ Nanoparticles;

[0055] S2, preparation of SiO2 nanoparticles: 10 parts by mass of tetraethyl orthosilicate, 40 parts by mass of anhydrous ethanol and 15 parts by mass of aqueous ammonia, prepare SiO2 nanoparticles by hydrolysis polymerization, stir for 6 hours, and then age at room temperature for 2 days. Finally, centrifuge to obtain SiO2 nanoparticles;

[0056] S3, preparation of sol: take 1 mass part of MgF2:Tb obtained in step S1 3+ The nanoparticles and 0.4 parts by mass of the SiO2 nanoparticles obtained in step S2 are dispersed in a mixed solvent of 20 parts by mass of isopropanol and 10 parts by mass of methyl isobutyl ketone, and after stirring evenly, 1 part by mass of pentaerythritol triacrylate and 0.1 part by mass of azobisisobutyronitrile are added and stirred evenly to obtain a composite sol;

[0057] S4, coating: coating the composite sol on the surface of the quartz glass by immersion pulling method at a speed of 75 mm / min for 3 times;

[0058] S5. Curing: Place the glass sample in an oven at 80°C for 5 minutes.

[0059] Example 2

[0060] This embodiment provides a composite material for a solar concentrator and a preparation method thereof:

[0061] Composite material for solar concentrator: comprising quartz glass, high molecular polymer, fluorescent material and scattering material, wherein the high molecular polymer, Tb 3+ , the masses of hollow MgF2 nanoparticles and SiO2 are:

[0062] High molecular weight polymer: 30 parts by mass;

[0063] Tb 3+ : 0.5 parts by mass;

[0064] Hollow MgF2 nanoparticles: 40 parts by mass;

[0065] SiO2 particles: 8 parts by mass, size 600nm;

[0066] The thickness of the high molecular polymer, fluorescent material and scattering material compositely coated on the surface of the fluorescent quartz glass is 700nm.

[0067] The preparation method comprises the following steps:

[0068] S1. Preparation of MgF2:Tb 3+ Nanoparticles: 15 parts by mass of magnesium acetate tetrahydrate, 0.25 parts by mass of Tb2O3, 40 parts by mass of n-propanol, 4 parts by mass of hydrofluoric acid and 4 parts by mass of hydrochloric acid, stirred vigorously and then poured into the polytetrafluoroethylene liner of the reactor, heated at 150°C for 6 hours, and after the reaction was completed, MgF2:Tb 3+ Nanoparticles;

[0069] S2, preparation of SiO2 nanoparticles: 15 parts by mass of tetraethyl orthosilicate, 60 parts by mass of anhydrous ethanol and 20 parts by mass of aqueous ammonia, prepare SiO2 nanoparticles by hydrolysis polymerization, stir for 6 hours, and then age at room temperature for 2 days. Finally, centrifuge to obtain SiO2 nanoparticles;

[0070] S3, preparation of sol: take 4 parts by mass of MgF2:Tb obtained in step S1 3+ The nanoparticles and 0.8 parts by mass of the SiO2 nanoparticles obtained in step S2 are dispersed in a mixed solvent of 40 parts by mass of isopropanol and 20 parts by mass of methyl isobutyl ketone, and after stirring evenly, 3 parts by mass of pentaerythritol triacrylate and 0.3 parts by mass of azobisisobutyronitrile are added and stirred evenly to obtain a composite sol;

[0071] S4, coating: coating the composite sol on the surface of the quartz glass by immersion pulling method at a speed of 150 mm / min for 3 times;

[0072] S5. Curing: Place the glass sample in an oven at 80°C for 10 minutes.

[0073] Example 3

[0074] This embodiment provides a composite material for a solar concentrator and a preparation method thereof:

[0075] Composite material for solar concentrator: comprising quartz glass, high molecular polymer, fluorescent material and scattering material, wherein the high molecular polymer, Tb 3+ , the masses of hollow MgF2 nanoparticles and SiO2 are:

[0076] High molecular weight polymer: 20 parts by mass;

[0077] Tb 3+ : 0.3 parts by mass;

[0078] Hollow MgF2 nanoparticles: 30 parts by mass;

[0079] SiO2 particles: 8 parts by mass, size 500nm;

[0080] The thickness of the high molecular polymer, fluorescent material and scattering material compositely coated on the surface of the fluorescent quartz glass is 600nm.

[0081] The preparation method comprises the following steps:

[0082] S1. Preparation of MgF2:Tb 3+ Nanoparticles: 12 parts by mass of magnesium acetate tetrahydrate, 0.15 parts by mass of Tb2O3, 40 parts by mass of n-propanol, 4 parts by mass of hydrofluoric acid and 4 parts by mass of hydrochloric acid were vigorously stirred and then poured into the polytetrafluoroethylene liner of the reactor and heated at 150°C for 6 hours. After the reaction was completed, MgF2:Tb 3+ Nanoparticles;

[0083] S2, preparation of SiO2 nanoparticles: 12 parts by mass of tetraethyl orthosilicate, 50 parts by mass of anhydrous ethanol and 18 parts by mass of aqueous ammonia, prepare SiO2 nanoparticles by hydrolysis polymerization, stir for 6 hours, and then age at room temperature for 2 days. Finally, centrifuge to obtain SiO2 nanoparticles;

[0084] S3, preparation of sol: take 2 parts by mass of MgF2:Tb obtained in step S1 3+ The nanoparticles and 0.6 parts by mass of the SiO2 nanoparticles obtained in step S2 are dispersed in a mixed solvent of 40 parts by mass of isopropanol and 20 parts by mass of methyl isobutyl ketone, and after stirring evenly, 3 parts by mass of pentaerythritol triacrylate and 0.3 parts by mass of azobisisobutyronitrile are added and stirred evenly to obtain a composite sol;

[0085] S4, coating: coating the composite sol on the surface of the quartz glass by immersion pulling method at a speed of 100 mm / min for 6 times;

[0086] S5. Curing: Place the glass sample in an oven at 80°C for 10 minutes.

[0087] Embodiments 4 to 7

[0088] The difference between Examples 4 to 7 and Example 1 is that the pulling speeds of the immersion pulling are 80 mm / min, 100 mm / min, 120 mm / min and 140 mm / min, respectively, and the corresponding coating thicknesses are 430 nm, 510 nm, 590 nm and 660 nm, respectively.

[0089] Comparative Example 1

[0090] The difference between Comparative Example 1 and Example 3 is that no high molecular polymer is added:

[0091] Composite material for solar concentrator: comprising quartz glass, fluorescent material and scattering material, the polymer, Tb 3+ , the masses of hollow MgF2 nanoparticles and SiO2 are:

[0092] Tb 3+ : 0.3 parts by mass;

[0093] Hollow MgF2 nanoparticles: 30 parts by mass;

[0094] SiO2 particles: 8 parts by mass, size 500nm;

[0095] The thickness of the fluorescent material and the scattering material compositely coated on the surface of the fluorescent quartz glass is 600nm.

[0096] Comparative Examples 2-3

[0097] The difference between Comparative Examples 2 and 3 and Example 1 is that the thickness of the coating is 200 nm and 300 nm, respectively.

[0098] Figure 1 This is a schematic diagram of the working principle of composite materials for solar concentrators. The figure shows that when sunlight hits the composite material, it is absorbed and converted by the fluorescent material, emitting light in all directions, and the scattering particles can also scatter sunlight to the quartz glass, thereby conducting it to the solar cell.

[0099] Figure 2 (a) is Tb prepared in Example 1 3+ Transmission electron micrograph of doped MgF2 nanoparticles, Figure 2 (b) is Tb 3+ Excitation spectrum of doped MgF2 nanoparticles, Figure 2 (c) is Tb in Example 1-4 3+ The emission spectrum of the doped MgF2 nanoparticles, the inset is a photograph of the sample in Example 1 under 365nm ultraviolet light. This shows that the fluorescent material with a low refractive index has been successfully prepared.

[0100] Figure 3 This is a scanning electron microscope photograph of the SiO2 particles prepared in Example 2. It can be seen that the size of the SiO2 nanoparticles is about 600nm and has a certain light scattering ability.

[0101] Figure 4(a) and (b) are scanning electron microscope images of the coatings prepared in Comparative Example 1 and Example 3, respectively. It can be clearly seen from the figure that without the composite of the polymer, the coating is loose. The composite coating has good compactness. In theory, the adhesion of the coating can be improved.

[0102] Figure 5 (a) and 5(b) are respectively microscopic photographs of the scratches of the coatings prepared in Comparative Example 1 and Example 3 under a 3H pencil. The experimental results can prove that the coatings composited with high molecular polymers have better adhesion.

[0103] Figure 6 (a) is the reflectance spectra of the samples prepared in Examples 1 to 3 and Comparative Examples 2 to 3, Figure 6 (b) to (d) are partial curves in 6(a). It can be seen that the reflectivity of quartz glass covered with 200nm to 700nm coating is lower than that of pure glass, which can reduce light scattering loss. In addition, the reflectivity of the coating with a thickness of 400 to 700nm is lower than that of 200nm. Moreover, the thicker the coating, the more light it absorbs.

[0104] Figure 7 This is a photograph of the composite material for solar concentrator prepared in Example 1 under 365nm ultraviolet light. It can be seen intuitively that the composite material can absorb ultraviolet light and emit it in all directions, so that it is conducted to the solar cell by the quartz glass.

[0105] Figure 8 The IV curves of the samples prepared in Examples 1 to 3. The experimental results show that the composite material for solar concentrators is coated on quartz glass, which can improve the conduction of sunlight and increase the photoelectric conversion efficiency of solar cells.

[0106] In summary, the composite material for solar concentrators has good adhesion on quartz glass, and can reduce reflectivity and increase light transmission performance under a specific coating thickness.

[0107] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.

Claims

1. A composite material for a solar concentrator, comprising quartz glass, a high molecular polymer, a fluorescent material and a scattering material, characterized in that: The high molecular polymer is formed by thermal curing of pentaerythritol triacrylate under the initiator of azobisisobutyronitrile; The fluorescent material is composed of Tb 3+ Doped hollow MgF2 nanoparticles; The scattering material is SiO2 particles of 400 to 600 nm; The high molecular polymer, fluorescent material and scattering material are compositely coated on the surface of the fluorescent quartz glass.

2. The composite material for solar concentrator according to claim 1, characterized in that: The high molecular polymer, Tb 3+ , the masses of hollow MgF2 nanoparticles and SiO2 are: High molecular weight polymer: 10 to 30 parts by weight; Tb 3+ : 0.2-0.5 parts by mass; Hollow MgF2 nanoparticles: 10-40 parts by mass; SiO2 particles: 4 to 8 parts by mass.

3. The composite material for solar concentrators according to claims 1 and 2, characterized in that: The thickness of the high molecular polymer, fluorescent material and scattering material compositely coated on the surface of fluorescent quartz glass is 400-700nm.

4. A method for preparing the composite material for solar concentrator according to claim 3, characterized in that: The following steps are involved: S1. Preparation of MgF2:Tb 3+ Nanoparticles: magnesium acetate tetrahydrate, Tb2O3, 40 parts by mass of n-propanol, hydrofluoric acid and hydrochloric acid, stirred vigorously and evenly, then poured into the polytetrafluoroethylene liner of the reactor, heated at 150-180°C for 6 hours, and after the reaction was completed, MgF2:Tb 3+ Nanoparticles; S2, preparation of SiO2 nanoparticles: tetraethyl orthosilicate, anhydrous ethanol and ammonia water, prepare SiO2 nanoparticles by hydrolysis polymerization, stir for 6 hours, and then age at room temperature for 2 days. Finally, centrifuge to obtain SiO2 nanoparticles; S3, preparation of sol: take the MgF2:Tb obtained in step S1 3+ The nanoparticles and the SiO2 nanoparticles obtained in step S2 are dispersed in a mixed solvent of isopropanol and methyl isobutyl ketone, and after being stirred evenly, pentaerythritol triacrylate and azobisisobutyronitrile are added and stirred evenly to obtain a composite sol; S4, coating: coating the composite sol on the surface of the quartz glass by 3 to 6 cycles of pulling by immersion pulling method; S5. Curing: Place the glass sample in an oven at 80°C for 5 to 10 minutes.

5. The method for preparing the composite material for solar concentrator according to claim 4, characterized in that: The added amounts of magnesium acetate tetrahydrate, Tb2O3, n-propanol, hydrofluoric acid and hydrochloric acid in step S1 are 10-15 parts by mass, 0.1-0.25 parts by mass, 40 parts by mass, 4 parts by mass and 4 parts by mass, respectively.

6. The method for preparing the composite material for solar concentrator according to claim 4, characterized in that: The added amounts of tetraethyl orthosilicate, anhydrous ethanol and aqueous ammonia in step S2 are 10-15 parts by mass, 40-60 parts by mass and 15-20 parts by mass respectively.

7. The method for preparing the composite material for solar concentrator according to claim 4, characterized in that: MgF2:Tb in step S3 3+ The added amounts of nanoparticles, SiO2 nanoparticles, isopropyl alcohol, methyl isobutyl ketone, pentaerythritol triacrylate and azobisisobutyronitrile are 1-4 parts by mass, 0.4-0.8 parts by mass, 20-40 parts by mass, 10-20 parts by mass, 1-3 parts by mass and 0.1-0.3 parts by mass, respectively.

8. The method for preparing the composite material for solar concentrator according to claim 4, characterized in that: The pulling speed of the immersion pulling method in step S4 is 75 to 150 mm / min.

Citation Information

Patent Citations

  • CaZnOS-MgF2 heterojunction stress luminescent material and preparation method thereof

    CN117384621A

  • Method for preparing film of elimination of reflection for PDP protection screen

    CN1757443A

  • Luminescent nanocomposites of rare-earth doped fluorides and graphene oxide using ionic liquid and method of preparation thereof

    IN201921025714A

  • Transparent luminescent solar concentrator

    US20210351312A1

  • Luminescent solar energy concentrator

    WO2013008186A2